2018
DOI: 10.1038/s41422-018-0048-0
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of linker histone H1.2 is essential for ATM activation and DNA damage repair

Abstract: Linker histone H1 is a master regulator of higher order chromatin structure, but its involvement in the DNA damage response and repair is unclear. Here, we report that linker histone H1.2 is an essential regulator of ataxia telangiectasia mutated (ATM) activation. We show that H1.2 protects chromatin from aberrant ATM activation through direct interaction with the ATM HEAT repeat domain and inhibition of MRE11-RAD50-NBS1 (MRN) complex-dependent ATM recruitment. Upon DNA damage, H1.2 undergoes rapid PARP1-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 64 publications
3
62
0
Order By: Relevance
“…The mechanisms underlying ATM inhibition have emerged recently. It has been shown that H1.2 and Bridging Integrator 1 (BIN1) attenuate ATM activation by directly interacting with ATM [47] or by indirect mechanisms involving E2F1 [48]. Notably, HITT expression is elevated 1 h after Dox treatment, which is later than ATM activation is detected (5 min).…”
Section: Plos Biologymentioning
confidence: 99%
“…The mechanisms underlying ATM inhibition have emerged recently. It has been shown that H1.2 and Bridging Integrator 1 (BIN1) attenuate ATM activation by directly interacting with ATM [47] or by indirect mechanisms involving E2F1 [48]. Notably, HITT expression is elevated 1 h after Dox treatment, which is later than ATM activation is detected (5 min).…”
Section: Plos Biologymentioning
confidence: 99%
“…In fact, H. pylori infection causes H3 Ser10 dephosphorylation and other histone modification changes that consequently affect the gastric epithelium and ultimately affect the pathogenicity of the bacterium (Ding et al 2010;Fehri et al 2009). Because several studies have shown that chromatin modifications, including certain types of histone modifications, are mechanistically and functionally relevant to ATM activation (Li et al 2018), it is tempting to speculate that H. pylori can also activate ATM through sophisticated histone modifications. These findings demonstrate that H. pylori infection triggers ATM activation through both activating ATM activity and increasing ATM protein levels.…”
Section: Helicobacter Pylori Triggers Atm Activationmentioning
confidence: 99%
“…Maintaining the integrity of the genome of mammalian preimplantation embryos, which can be damaged by both internal and external factors, is critical for normal preimplantation and subsequent development. Epigenetic factors contribute to the maintenance of genome stability, e.g., by preventing excessive activation of ATM by linker histone H1.2 and promoting DNA damage repair by histone-modifying enzymes G9a or SETD8 [ 5 , 7 , 14 ]. However, few studies have examined the relationship between epigenetics and genomic integrity during mouse preimplantation development.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic alterations such as histone modifications and localization of linker histones contribute to DNA damage repair [ 5 , 6 , 7 ]. Histone H4K20 methylation is conserved from yeast to human; H4K20 can be monomethylated by SETD8/PR-SET7 and di- and trimethylated by SUV4-20H1 and SUV4-20H2 [ 8 , 9 , 10 , 11 ].…”
mentioning
confidence: 99%